The Role of knowledge Management in Promoting the Quality of Higher Education from Faculty Members Point of View: Faculty of Economic, Commercial and Management Sciences, Laghouat, Algeria - حلموس, الأمين (Milev Journal of Research and Studies, 2019)
This study aimed to examine the knowledge management processes (knowledge generation, knowledge storage, knowledge distribution and knowledge application) and show their role in creating and enhancing quality to the professors of economics, trade and science of management at the University of AmmarTeledji in laghouat , In this study I used SPSS program, to test hypotheses by using a combination of statistical methods and we have been reached for a range of outcomes, including: that the knowledge management processes have a role in creating and enhancing quality and this is explained by the coefficient of determination R ², which was equal to: 0.424 indicates that knowledge management processes explains 42.4% of the dependent variable: quality, especially when it comes to the application of knowledge.